2019
DOI: 10.3390/app9204413
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approach to Manufacture an AUV Propeller by Additive Manufacturing and Error Analysis

Abstract: Autonomous underwater vehicle (AUV) is an unmanned tether-free vehicle which is powered by battery or fuel cell. The weight of the AUV is a major issue to be decided when considering its performance. To manufacture a propeller that is lighter in weight and able to carry the pressure applied to the blades is an involving process. The present study investigates the performance of the propeller of an AUV, manufactured by additive manufacturing, using ABS plastic material. The propeller blade designed in SolidWork… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Designing of the AUV propeller is the challenging task since propeller blades have a very complex profile. A 3D CAD model with hexahedron free mesh configuration was developed using SOLID WORKS SP47 to ensure mesh independence in the propeller blades for AUV 22 . For the analysis of the metal forming process and the temperature raised during the forming process, DEFORM-F33D simulation tool was used.…”
Section: Methodology (A) Solid Modelling and Analysis Of Auv Propelle...mentioning
confidence: 99%
See 2 more Smart Citations
“…Designing of the AUV propeller is the challenging task since propeller blades have a very complex profile. A 3D CAD model with hexahedron free mesh configuration was developed using SOLID WORKS SP47 to ensure mesh independence in the propeller blades for AUV 22 . For the analysis of the metal forming process and the temperature raised during the forming process, DEFORM-F33D simulation tool was used.…”
Section: Methodology (A) Solid Modelling and Analysis Of Auv Propelle...mentioning
confidence: 99%
“…Modular blades and the hub is shown in Figure 4. In an earlier study 22 , the AUV propeller was manufactured in five stages, shown in Figure 5. In contrast, in the present study, the 3DP AUV propeller is made in one single operation with ease using FDM, compared with the conventional method.…”
Section: (B) Fdm Processmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of propeller manufacturing, 3D printing technology has a certain research base. Khaleed et al developed a propeller manufacturing method for autonomous underwater vehicles by fused deposition modeling [ 29 ]. He et al used wire arc AM to obtain metal propellers that gave better mechanical properties than those of cast propellers [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this work we focus on thermoplastics. It has been used to produce small scale propellers for Small Unmanned Aerial Vehicles (SUAV's) [6][7][8][9], and for large-scale 3D printing, it is slowly coming to the fore as a cost-effective solution for manufacturing large parts and components.…”
Section: A Introductionmentioning
confidence: 99%